Numerical simulation and experimental investigation on tribological performance of SiC surface with squamous groove micro texture. (27th May 2022) - Na, Zhang; Zhentao, Li; Muming, Hao; Yancong, Liu; Baojie, Ren; Wang, Zengli
Abstract: To improve the tribological characteristics of the face seal, the squamous groove micro textures with different area proportion and the circular dimple micro texture were designed and manufactured. The disc‐disc friction and wear experiments and numerical simulation were carried out in oil lubrication. The pressure distribution, friction coefficient, fluid temperature and wear morphology are investigated. The study show that the friction coefficients of the micro textured and untextured samples decline with the increase of load, but first increase and then decrease with the rise of rotational speed. Micro textured samples could decline the friction coefficient effectively, and the asymmetric structure in the lubricant inflow and outflow region of the squamous groove micro texture makes it have better tribological performance. In addition, the micro texture can increase heat dissipation area, reduce heat production and collect wear debris, which could modify the lubricant temperature and wear morphology effectively.